Forest and water governance in Sweden - Berglund, Emma (SLU/Dept. of Forest Products, 2014)
Water related problems are highlighted as a challenge to sustainable development and the topic of forests and water is gaining increased attention worldwide. Governing forest and water is a complex issue, as the interactions are affected by policies and actors from multiple levels and sectors. In Sweden, forests cover much of the land and forestry is an important land-use, inevitably impacting the water in the landscape. This study aims to understand and explain the existing governance framework around forestry and water in Sweden. Based on the Policy Arrangement Approach, the study’s research questions focused on the actors involved, the formal and informal rules, the resources and power structures and the discourses related to forestry and water in Sweden. To answer the research questions qualitative document analysis and interviews with relevant actors from different actor groups were undertaken. As a smaller part of the study discourses on the management level where examined by qualitative interviews with forestry practitioners.